2017
DOI: 10.1364/oe.25.003454
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of static convergence and accommodation responses to images of integral photography and binocular stereoscopy

Abstract: Static convergence and accommodation responses were measured by comparing integral photography images, binocular stereoscopic images, and real objects in a measurement range from 450 to 900 mm. The experimental results were evaluated with a multiple comparison test. It was found that six of the ten observers did not have an accommodation-convergence conflict in viewing integral photography in the range. Moreover, the required resolution was found to be 0.7 or more and less than 1.4 cycles per degree for induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…The SMV condition means that two or more light rays from the point lights of the reconstructed 3D objects reach the pupil of an observer. Hiura et al [56] showed that six of the ten observers did not have an accommodation-convergence conflict in viewing integral photography in the range. Moreover, the required resolution was found to be 0.7 or more and less than 1.4 cycles per degree for inducing accommodation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The SMV condition means that two or more light rays from the point lights of the reconstructed 3D objects reach the pupil of an observer. Hiura et al [56] showed that six of the ten observers did not have an accommodation-convergence conflict in viewing integral photography in the range. Moreover, the required resolution was found to be 0.7 or more and less than 1.4 cycles per degree for inducing accommodation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the convergence and accommodation responses have been predicted to be consistent with the depth position of the 3D target. The accommodation response to integral 3D displays has been theoretically investigated by many researchers [53][54][55][56]. The reports indicate that satisfying the super multi-view (SMV) condition is the most important requirement for obtaining a proper accommodation response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent research, we measured the accommodation and convergence responses to I3D targets. 10 In that research, the responses to I3D targets were found to be nearly the same as those to real targets. However, the resolution dependency on the depth perception was not verified in the case viewing of the I3D target, and neither were the depth perception or accommodation-convergence conflict.…”
Section: Introductionmentioning
confidence: 80%
“…Although the ocular accommodation driven by 3D displays were discussed in many studies [11][12][13][14][15][16][17][18], the relaxing of accommodation in hyperopic objects has never been studied. Because that measuring hyperopia in children is often masked by accommodation, and hyperopia is a significant risk factor of developing amblyopia, it is important to relax children's accommodation for accurate assessment.…”
Section: Accommodation Testmentioning
confidence: 99%